2012
DOI: 10.1007/s00261-012-9974-3
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic cholangiocarcinoma: relationship between tumor imaging enhancement by measuring attenuation and clinicopathologic characteristics

Abstract: Purpose: Arterial enhancement of intrahepatic cholangiocarcinoma (ICC) has been noted. To precisely identify the characteristics of tumor enhancement patterns, we examined the relationship between CT attenuation in the tumor and clinicopathological parameters or prognosis.Methods: Subjects were 42 ICC patients who had undergone hepatectomy. Microvessel density (MVD) determined by CD34 staining was compared with imaging. Attenuation was calculated in images from multi-detector CT of tumor and non-tumorous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Although IMCC is typically hypovascular, IMCC arising from chronic viral hepatitis and the cirrhotic or pre-cirrhotic liver is more likely to be hypervascular after the malignant transformation of the cholangiocytes [27]. It has been reported that hypervascular versus hypovascular IMCC on arterial phase CT correlates with reduced malignant behaviour and better survival [13][14][15]28]. In a previous study, welldifferentiated tumours were found to have greater enhancement on gadoxetic acid-enhanced MRI than moderately or poorly differentiated IMCCs [16].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although IMCC is typically hypovascular, IMCC arising from chronic viral hepatitis and the cirrhotic or pre-cirrhotic liver is more likely to be hypervascular after the malignant transformation of the cholangiocytes [27]. It has been reported that hypervascular versus hypovascular IMCC on arterial phase CT correlates with reduced malignant behaviour and better survival [13][14][15]28]. In a previous study, welldifferentiated tumours were found to have greater enhancement on gadoxetic acid-enhanced MRI than moderately or poorly differentiated IMCCs [16].…”
Section: Discussionmentioning
confidence: 93%
“…There have been a few reports indicating that the imaging findings of IMCC correlate with prognosis [12][13][14][15]. IMCCs with abundant tumour fibrous stroma, defined as "scirrhous type", exhibit a delayed enhancement area on CT, which correlates with poor prognosis [12].…”
Section: Introductionmentioning
confidence: 98%
“…Two studies including 42 and 70 patients with iCC and operative resection showed strong correlations between augmented arterial tumour enhancement in preoperative CT, histopathological vascularity, and higher survival rate. Histological examination of these tumours demonstrated a smaller amount of fibrotic tissue and necrosis but a higher cellularity [30,31]. The estimated overall accuracy of CT in evaluating tumour resectability ranges between 60 and 75% [32,33].…”
Section: Computed Tomographymentioning
confidence: 99%
“…This hypervascular appearance has been suggested to correlate with highly cellular tumors containing less fibrous components or a more vascular component intermixed with the fibrous tissue, smaller size, and a better prognosis [26,[28][29][30], and is also more prevalent in cholangiocarcinoma that develops in cirrhotic liver [15]. This hypervascular appearance was seen in all of the lesions in our cohort.…”
Section: Discussionmentioning
confidence: 55%